CHANGES IN MUSCLE-SPECIFIC MICRORNAS ACCOMPANY TERMINAL STAGES OF MONOCROTALINE-INDUCED PULMONARY HYPERTENSION IN RAT. (April 2021) - Kmecova, Zuzana; Veteskova, Jana; Zirova, Katarina; Pivackova, Lenka Bies; Doka, Gabriel; Malikova, Eva; Krenek, Peter; Passakova, Nina; Paulis, Ludovit; Luknar, Milan; Goncalvesova, Eva; Klimas, Jan
Abstract : Objective: Importance of muscle-specific microRNAs (miR-1/miR-133a/miR-208/miR-499) has been identified in various cardiovascular pathologies, including their potential of being biomarkers in these diseases. Pulmonary arterial hypertension (PAH) is an incurable disease progressing into right ventricular (RV) failure as the leading cause of death. Here, we hypothesised that muscle-specific microRNAs influence RV damage in PAH and their plasma levels might be used also as indicators of disease severity. Design and method: 12-weeks old male Wistar rats were administered either monocrotaline (MCT group) or vehicle (CON group) and the animals were sacrificed 4 weeks after this treatment. Certain animals from MCT group, in which the condition of pulmonary hypertension (PH) developed more severely, were terminated prematurely (ptMCT group), since they displayed signs of serious clinical worsening and so represented the terminal stage of PH. Additionally, plasma samples of patients diagnosed with PAH were obtained from a PAH referral centre. Expression of microRNAs, both in rats and humans, was determined by RT-qPCR. Results: Fulton index of MCT and ptMCT animals was gradually increased by 47% (p < 0.05 vs CON) and by 110% (p < 0.05 vs CON and MCT) respectively. Expression of muscle-specific microRNAs in RV was not significantly altered in MCT group, but we noted decrease in ptMCT group (-52% for miR-1, -61% for miR-133a, -64% for miR-208, -57% for miR-499 vs CON, all p < 0.05). In human plasma samples, only miR-1 and miR-133a expressions were reliably determinable by RT-qPCR, nevertheless, we noted no significant correlations with mean pulmonary arterial pressure, pulmonary vascular resistance, RV cardiac output or NT-proBNP levels. Conclusions: The decrease of muscle-specific microRNAs in ptMCT group suggests that they might not be responsible for RV modifications in earlier stages of developed PH, but their downregulation in RV tissue mirrors the severity of terminal stages of this experimental model. On the other hand, based on our results, the use of muscle-specific microRNAs as clinical biomarkers of PAH remains elusive and the attention should be directed to other miRNA candidates.